2015
DOI: 10.1021/acs.jafc.5b00012
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation Potentials of Perfluoroalkyl Carboxylic Acids (PFCAs) and Perfluoroalkyl Sulfonic Acids (PFSAs) in Maize (Zea mays)

Abstract: Uptake of perfluoroalkyl acids (PFAAs) by maize represents a potential source of exposure for humans, either directly or indirectly via feed for animals raised for human consumption. The aim of the following study was, therefore, to determine the accumulation potential of perfluoroalkyl carboxylic acids (PFCAs) and perfluoroalkyl sulfonic acids (PFSAs) in maize (Zea mays). Two different concentrations of PFAAs were applied as aqueous solution to the soil to attain target concentrations of 0.25 mg or 1.00 mg of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 26 publications
8
62
0
2
Order By: Relevance
“…If we again use the USEPA RfD for PFOA for PFBS, PFHpA, and PFNA, a single radish root serving could meet the RfD at soil concentrations of 2.5 ± 1.0 ng/g for PFBS, 1.4 ± 0.4 ng/g for PFHpA, and 4.9 ± 1.3 ng/g for PFNA. There is some evidence that PFAA availability may be concentration dependent and that these relationship may vary with PFAA and mixtures (Krippner et al 2015). Accordingly, measured BCF values in plant tissues may be larger or smaller than the values found in the present study depending on the specific PFAA and its soil concentration.…”
Section: Resultsmentioning
confidence: 99%
“…If we again use the USEPA RfD for PFOA for PFBS, PFHpA, and PFNA, a single radish root serving could meet the RfD at soil concentrations of 2.5 ± 1.0 ng/g for PFBS, 1.4 ± 0.4 ng/g for PFHpA, and 4.9 ± 1.3 ng/g for PFNA. There is some evidence that PFAA availability may be concentration dependent and that these relationship may vary with PFAA and mixtures (Krippner et al 2015). Accordingly, measured BCF values in plant tissues may be larger or smaller than the values found in the present study depending on the specific PFAA and its soil concentration.…”
Section: Resultsmentioning
confidence: 99%
“…There are various reports which have indicated the prevalence of PFASs (i.e., PFOA, PFOS, and PFBS) in several environmental matrices, including plants. For instance, Mudumbi et al [28] reported the susceptibility of riparian plants to PFOA accumulation in South Africa, Western Cape Province (WCP), while Krippner et al [35,36] indicated higher uptake of PFASs, including PFBS, into plant leaves. Recently, Kurwadkar et al [37], as well as Zhao and Zhu [38], addressed the uptake of PFASs in plants.…”
Section: Resultsmentioning
confidence: 99%
“…Wastewater-borne micro-contaminants can also be taken up by plants [46][47][48][49][50][51] and may reach the food chain. Accumulation in the edible parts of fruits and vegetables as already described for perfluorinated and polyfluorinated alkyl substances [52][53][54] has to be considered also for other micro-contaminants. However, there is still a lack of knowledge on the fate and transport for most of organic micro-contaminants in arable soil systems, on root interactions and plant uptake [55].…”
Section: Chemical Risksmentioning
confidence: 99%